Coping with COVID-19-induced threats to self. (February 2021) - Kruglanski, Arie W.; Molinario, Erica; Lemay, Edward P.
Whereas the COVID-19 pandemic induces in people both uncertainty and angst, the latter may not be a direct consequence of uncertainty as such, but rather of the possible negative outcomes whose subjective certainty increased under the pandemic. From this perspective, we discuss the psychological determinants of people's reactions to the pandemic and their modes of self-affirmation in response to pandemic-implied threats. Those reactions are guided by value-oriented narratives that may variously drive people's pro- and anti-social behaviors during the pandemic.